Unemployment and the Rate of Change of Money Wage Rates in the United Kingdom 1862-1963: A Reappraisal - Hines, A. G. (The Review of Economics and Statistics, 1968)
n a pioneering paper in 1958 Phillips [6] advanced the proposition that in the United Kingdom there is a statistically significant relationship between the level and the rate of change of unemployment (U and A U) and the rate of change of money wage rates (AW) which has been remarkably stable during the hundred years since 1862.1 Phillips, Lipsey [5] and others have advanced theoretical grounds on which it has been concluded that unemployment is the causal variable in the observed relationship. There is reason to believe that this proposition is widely accepted today and there is evidence to suspect that it has reinforced arguments in favour of controlling the price level through the level of unemployment. The Phillips hypothesis has been the subject of considerable discussion. Kaldor [3] in 1959 accepted the empirical evidence which supports it but disputed the postulated chain of causation. His argument may be taken to mean that the observed relationship between AW and U is consistent with the hypothesis of no causal connection between the two variables since, within certain limits, both could be concomitants of variations in the level of activity. Dicks-Mireaux and Dow [1] in 1959, Hines [2] in 1964, and others have drawn attention to factors such as the rate of change of the price level (AP) and the rate of change of the percentage of the labour force unionised (AT) which may affect AW independently of U and AU. Knowles and Winsten [4] in 1959, doubted whether the results of Phillips had any implication for public policy. They observed that, on his own data, the critical range of unemployment, between 0 and 3 'A per cent of the labour force, is compatible with any range of inflation between 2 per cent and 28 per cent per annum, while a stable wage level is compatible with between 2 per cent and 22 per cent of the labour force being unemployed. In this paper, we propose to re-examine the hypothesis and the statistical evidence concerning the relationship between the level of unemployment and the rate of change of money wage rates. Specifically, it will be shown that although there was a strong relationship between unemployment and changes in money wage rates in the 19th century, in subsequent years, the association has been very much weaker. Moreover, in the post 19th century years, the level of unemployment does not make a significant contribution to the explanation of the variance in money wage rates in models which include such variables as changes in the cost of living and the level and the rate of change of unionisation. Further, when the coefficients of the unemployment variables are used to predict subsequent values of AW conditional on U and AU, rather poor predictions are obtained. It will be suggested that there are good reasons why these results should have been obtained. In the years since the 19th century, new institutions and relationships have come to dominate the wage bargain. Since unemployment is now a relatively unimportant determinant of wage rate changes, its role in the control of wage inflation must in consequence be severely reduced.